The Roman partisan struggle and the role of the Numidian King Juba Ier in its events - Bouchama, khaoula; belabed, zineb (The Algerian Historical Journal, 2026)
Through this article, we try to shed light on the Roman partisan conflict that negatively affected North Africa, and it erupted between the Roman leaders in order to spread their expansionist policy, and the rebellious Numidian king also included “juba Ier” as a party to it, when he wanted to restore the province that M. Occupied by the Romans after the fall of Carthage 146 BC. We will also try to find out, besides the reasons for the outbreak of this conflict, the role played by the Numidian King Juba Ier in it, so that we can stand the impact he had on Numidia..